ANALISIS DESKRIPTIF PENGGUNAAN HIJAB ANTARA SYARIAT DAN TREN FASHION - Ahmad Burhanuddin; Sawaluddin Siregar; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
This article discusses hijab in the Qur'anic perspective, highlighting its role as a symbol of obedience and identity for Muslim women. The author explains that wearing the hijab is an obligation that has deep meaning, not only as a covering of the aurat, but also as protection and a sign of modesty. Although the hijab is seen as an obligation, there is debate over the interpretation of the Qur'anic verses that regulate its wearing. This study uses qualitative methods and a tafsir approach to explain the relationship between hijab and women's freedom, as well as how Islamic feminism sees hijab as a choice that reflects women's independent social identity. The hijab not only functions in a religious context, but also plays a role in complex social dynamics, becoming a statement of freedom and self-expression for Muslim women. As such, the hijab presents multiple meanings that evolve with the times, while questioning how women respond to religious obligations while maintaining their individual rights and freedoms in dress.